Akibat Hukum Terhadap Ahli Waris Yang Tidak Ditetapkan Sebagai Penerima Waris - R Kurniawan Bagus W; Sumiati; Sangrila Puspita; Kantrey Sugiarto (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract— This scientific article aims to find out the legal consequences for heirs who have the right to inherit but are not stipulated in the determination of the Polewali Religious Court No.444/Pdt.G/2015/PA.Pwl. The method used in this article is normative juridical, which is a method that is focused on examining the rules or norms in positive law. The normative juridical method does not start from a hypothesis, but departs from identifying legal facts and eliminating irrelevant matters to be determined as legal issues to be solved. The results in the conclusion indicate that the position of the nephew as a substitute heir who is not designated as an heir in the Islamic inheritance system according to the Compilation of Islamic Law based on the Determination of the Polewali Religious Court Number 444/Pdt.G/2015/PA.Pwl, is the occurrence of a substitute heir who does not being determined as the beneficiary of the heir is possible because of the facilities in the form of facilities and infrastructure which include legal counseling materials, and the smooth administration is not supportive which consequently has an impact on the low awareness of the public in complying with the provisions of the substitute heir or whether something has been missed and or is not too thorough from the judge, so that cause various problems that cause heirs who may have more rights such as substitute heirs do not get their rights.